(untitled) (Publicaciones en Ciencias y Tecnología, 2007)
We construct for each pair of compact oriented manifolds Y and M the category H(MS(Y)) of homologies of Y-branes extended between D-branes embedded in M using transversal intersecttion in the sense of Chas and Sullivan. AMS Subjec-classification: 18D35, 18G35, 18G55, 57R90.